Performance investigation of a transparent roof forced convection solar drying system for drying Andrographis paniculata - Yuyen, Kotchanipha; Nabnean, Sarawut (Bulletin of Applied Sciences, 2026)
This research investigated the performance of a transparent roof forced convection solar drying Andrographis paniculata (commonly known as “Fah Talai Jone”). The system was designed as a large-scale greenhouse with an area of 3×12 m2. The roof structure consisted of alternating transparent and opaque corrugated metal sheets, each measuring 50×120 cm2, while the walls were constructed from concrete blocks enclosing all four sides. The ventilation system comprised 6 fans powered by two 80 watt photovoltaic panels. In the experiment, a total of 200 kg of Andrographis paniculata was dried using the system between 8:00 a.m. and 6:00 p.m. The average solar radiation intensity during the experimental period was 366 W/m2. Drying system temperature ranged from 36 - 41 °C, which is suitable for herbal processing as it prevents thermal degradation. The initial moisture content of 82% (wb) was successfully reduced to 10% (wb) within only three days. In comparison, natural sun drying achieved a final moisture content of 22% (wb). Thae solar dryer compared to natural sun drying a 40% reduction in drying time. The dried Andrographis paniculata obtained from the solar dryer demonstrated superior quality in terms of bioactive compound retention, color attributes, and a water activity of 0.41, which allows for extended storage stability by reducing the risk of fungal growth. Furthermore, the system effectively prevented insect infestation, rainfall interference, and dust contamination, ensuring a more hygienic and reliable drying process.